2003
DOI: 10.1152/ajpendo.00350.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intracerebroventricular infusion of MCH causes obesity in mice

Abstract: Melanin-concentrating hormone (MCH) is a cyclic amino acid neuropeptide localized in the lateral hypothalamus. Although MCH is thought to be an important regulator of feeding behavior, the involvement of this peptide in body weight control has been unclear. To examine the role of MCH in the development of obesity, we assessed the effect of chronic intracerebroventricular infusion of MCH in C57BL/6J mice that were fed with regular or moderately high-fat (MHF) diets. Intracerebroventricular infusion of MCH (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(125 citation statements)
references
References 34 publications
5
118
0
2
Order By: Relevance
“…infusions of either MCH or an MCH-1 receptor antagonist had no effect on daily home-cage activity [12,17,[36][37][38]. It should be noted, however, that in three of these studies, chronic MCH treatment failed to increase food intake [12,36,37]. Clearly, additional studies are required to better understand the impact of acute versus chronic administration of MCH on food intake and locomotor energy expenditure.…”
Section: Discussionmentioning
confidence: 93%
“…infusions of either MCH or an MCH-1 receptor antagonist had no effect on daily home-cage activity [12,17,[36][37][38]. It should be noted, however, that in three of these studies, chronic MCH treatment failed to increase food intake [12,36,37]. Clearly, additional studies are required to better understand the impact of acute versus chronic administration of MCH on food intake and locomotor energy expenditure.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that the expression level of MCH mRNA increases in leptin-deficient obese (ob/ob) mice as well as in response to fasting in wild-type mice (Qu et al, 1996). It is also been shown that intracerebroventricular administration of MCH causes a rapid increase in food intake (hyperphagia) and obesity (Gomori et al, 2003). Genetic models further confirm the role of MCH in energy homeostasis.…”
Section: Introductionmentioning
confidence: 79%
“…Processing of Pmch results in the production of three neuropeptides: neuropeptide glycine-glutamic acid (N-GE), neuropeptide glutamic acid-isoleucine (N-EI), and MCH (41). Pmch mRNA is upregulated after fasting or leptin deficiency (32, 50); third ventricle intracerebroventricular injections of MCH increase food intake and body weight (11,19,22,28,53); Pmch knockout mice are lean due to a decreased food intake and an increased metabolic rate (31, 59); and overexpression of MCH causes obesity (35). In rodents MCH binds to melanin-concentrating hormone receptor 1 (MCH1R), a G protein-coupled receptor expressed throughout the brain (7,33,55,56).…”
mentioning
confidence: 99%